Konsep Peserta Didik Dalam Al-Qur’an (Analisis Tarbawi Atas Q.S Al-Mujadilah: 11) - Adnin, Gina Fauzia; Surahman, Cucu; Sumarna, Elan (Jurnal El-Thawalib, 2024)
Students from an Islamic education perspective are individuals who are growing and developing, both physically, mentally, socially and spiritually in navigating life in this world. Islamic education seeks to instill faith values that not only lead to mastery of knowledge, but also to the formation of noble morals and the practice of religion in everyday life. However, many students are not yet fully able to apply religious values in their lives, especially in facing various challenges in an increasingly complex and digitally connected world. Therefore, students are expected not only to master knowledge academically, but also to be able to practice this knowledge with a strong moral foundation and faith values. This research aims to analyze the content of the holy verses of the Koran related to the application of educational values that can improve students' morals, as well as indicators that must be considered in the learning process according to Islamic teachings. This research uses a literature study method (library research) to examine students' concepts from the perspective of the Al-Qur'an, especially the interpretation of Surah Al-Mujadilah verse 11. The results of this research are expected to provide a comprehensive picture of how students are positioned in Islamic education, as well as providing an in-depth view of their roles and responsibilities in the educational process according to the perspective of the Koran and tarbawi interpretation. This research will also explore ways that can increase the practice of religious values among students, to create a generation that is not only intellectually intelligent, but also superior in character and morality